The three solutions of the equation f(x) = 0 are -2, 0, and 3. Therefore, the three solutions of the equation f(x - 2) = 0 are
so we have to do so> If f(x) = 0 at x = -2, 0 and 3 then f(x - 2) = 0 for x - 2 = -2 , x - 2 = 0 and x - 2 = 3 Solve the above equations to find and you will have your answer! x = 0 , x = 2 and x = 5
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?